ICT utilization among homeschooling families with adolescents a phenomenographic study - Maaghop, Ma. Consuelo C. (College of Education, University of the Philippines Diliman, 2021)
This phenomenographic research studied the varied ICT use of Filipino homeschooling parents, their adolescents and their contextual background. For parents the categories of description were as consumers, filters, and instiller of values in using technology with the themes of expanding awareness on communication, facility for learning and monitoring the consumption of the adolescent. For adolescents, the categories were as consumer learner and seeker of their own potential with themes on communication, entertainment & gaming, access & restrictions and participating in homeschooling. The categories for family dynamics were consumers, learners, and managers of technology and themes on communication, digital literacy and character building. The study recommends that providers promote digital literacy and capacity building for independent learning, parents prepare adolescents to productively participate in the digital community and educational technologists to design learning materials and spaces, especially in Filipino and Araling Panlipunan, encouraging digital fluency and opportunities for responsible digital citizenship.